Physical activity and its associated factors among secondary school students - Jaafar, Juhaida (2018)
Introduction: Physical activity refers to any body movement that requires energy expenditure. The suggested time for physical activity for adolescents is 60 minutes per day. The risk for obesity and other non-communicable disease increases for those not physically active. Objective: This study is to determine the level of physical activity and its associated factors among secondary school students in Terengganu. Methods: A cross sectional study was conducted in August 2016 involving form one and form two students from six government secondary schools. Multistage stratified cluster sampling was employed. The data were collected using Physical Activity Questionnaire for Children (PAQ-C) (Malay version) and Body Image Contour Drawing Rating Scale. Data were analysed by single and multiple logistic regression using SPSS version 22. Result: A total of 603 students were involved with response rate 89.7%. About 52.9% of the students were physically inactive. Multiple logistic regression analysis shows that being female [OR (95% CI): 5.07 (3.57, 7.20)] and time allocated for study [OR (95% CI): 0.86 (0.75 , 0.98)] were associated with physical inactivity. Conclusion: Majority of adolescents were physically inactive. Physically inactive students allocate less time for study and mostly were female.